Wall Chart Dewata Nawa Sanga Sebagai Media Pembelajaran Agama Hindu Bernilai Teo-Estetis - I Putu Agus Aryatnaya Giri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Media is an indispensable component in the learning process, especially Hinduism, in this case the media is used to transmit messages from the sender (communicator / educator / media) to the recipient (communicant / student) in order to stimulate thoughts, feelings, attention or the will of students so that later it will encourage the learning process. The purpose of this study was to analyze the theo-aesthetic value of Dewata Nawa Sanga's wall chart learning media using qualitative research methods. The conclusion of the research shows that the Dewata Nawa Sanga wall chart is a learning medium that is full of theo-aesthetic values, which means that the media contains elements of theology (knowledge of divinity) framed with aesthetic values (art / beauty of pictures and colors) which aim for students who see to be interested in learning it as well as clarifying the definition of verbal with visual media. Dewata Nawa Sanga, also known as Nawa Dewata (nine divine figures), are nine divine figures who are worshiped as guardians of the nine cardinal directions in the teachings of Hinduism in Bali. In the world of Hindu religious education, especially regarding the Gods, Nawa Sanga has a very important role which is intended to shape students into human beings who believe and fear God Almighty and have noble character.